Comparison of common platelet receptors between the chacma baboon (Papio ursinus) and human for use in pre-clinical human-targeted anti-platelet studies. (18th May 2016) - Janse van Rensburg, Walter J.
Abstract: Anti-platelet agents play a central part in the treatment and prevention of acute thrombotic events. Discriminating animal models are needed for the development of novel agents. The chacma baboon has been extensively used as a model to evaluate anti-platelet agents. However, limited data exist to prove the translatability of this species to humans. We aimed to determine the suitability of the chacma baboon in preclinical human targeted GPIIb/IIIa, GPIbα and P2Y12 studies. Light-transmission platelet aggregometry (LTA), whole blood impedance aggregometry, receptor number quantification and genomic DNA sequencing were performed. Baboon ADP and arachidonic acid-induced LTA aggregation results differed significantly from human values, even at increased concentrations. LTA ristocetin-induced agglutination was comparable between species, but baboon platelets needed twice the concentration of ristocetin to elicit a similar response. Citrated baboon blood had significantly less aggregation than humans when evaluated with impedance aggregometry. However, hirudinised baboon whole blood gave similar aggregation as humans at the same agonist concentrations. GPIIb, GPIIIa and GPIbα numbers were significantly more on the baboon platelets. None of the amino acids deemed vital for receptor function, ligand binding or receptor inhibition, were radically different between the species. However, a conservative change in a calcium-binding region of GPIIb may render the baboon platelets more sensitive to calcium-binding agents. The chacma baboon may be used for the evaluation of human-targeted GPIIb/IIIa-, GPIbα- and P2Y12-inhibiting agents. However, the best anticoagulant, optimal agonist concentrations, increase in receptor number and sequence differences must be considered for any future studies.